Sifat filler kayu keruing terhadap vulkanisat karet - Herminiwati Herminiwati; Nursamsi Sarengat; Purnama Darmadji; Widya Meidrianto (Majalah Kulit, Karet, dan Plastik, 1999)
The purpose of this research was to investigate the properties of keruing wood filler in their application on vulacanized rubber of shoes soles. To know its suitability for rubber goods filler, the properties of keruing wood filler was investigated by comparing with carbon black N330. Keruing wood filler were made by carbonization process at temperature 450oC for one hour and activation process with NaCl 4% for twenty four hours, followed by pyrolisis at temperature 500oC for one hour. Filler were milled and sieved by 400 mesh siefter. The standard compound formula was prepared base on ASTM D 3192 with various filler level of keruing wood filler, carbon black N330 either separately formulated of combination. The research showed that using keruing wood filler in the amount of 30-70 phr could meet 75% the requirements of SNI. 12-0172-1987 : Canvas shoes for general purpose, where as carbon black N330 in the amount of 30-70 phr could meet 87,5% the requirements of SNI. 12-0172-1987. Combination of keruing wood filler and carbon black showed that keruing wood filler could substitute 25-57 phr of carbon black.